1997
DOI: 10.1175/1520-0493(1997)125<0831:asotpo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Predictability of Tropical Pacific SST in a Coupled Atmosphere–Ocean Model Using Singular Vector Analysis: The Role of the Annual Cycle and the ENSO Cycle*

Abstract: The authors examine the sensitivity of the Battisti coupled atmosphere-ocean model-considered as a forecast model for the El Niño-Southern Oscillation (ENSO)-to perturbations in the sea surface temperature (SST) field applied at the beginning of a model integration. The spatial structures of the fastest growing SST perturbations are determined by singular vector analysis of an approximation to the propagator for the linearized system. Perturbation growth about the following four reference trajectories is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
94
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 27 publications
19
94
0
Order By: Relevance
“…2.1a and Fig. 2.1b are similar to that in the SV1 and FP of the Battisti coupled atmosphere-ocean model (Chen et al 1997) and an older version of the ZC model (Xue et al 1997a). …”
Section: R(tt + At) = ^-supporting
confidence: 63%
See 4 more Smart Citations
“…2.1a and Fig. 2.1b are similar to that in the SV1 and FP of the Battisti coupled atmosphere-ocean model (Chen et al 1997) and an older version of the ZC model (Xue et al 1997a). …”
Section: R(tt + At) = ^-supporting
confidence: 63%
“…Xue (1997a, b) constructed a forward tangent linear model for the ZC model using a Markov model and multi-variable EOF method performed on the reduced model physical space. Their SV spatial distribution was similar to that in Chen et al (1997). Fan et al (2000), using a different intermediate complexity coupled model, found that optimal error growth depends critically on the seasonal cycle and ENSO phase as well as the lead time of prediction.…”
mentioning
confidence: 59%
See 3 more Smart Citations